High thermopower and birefringence in layered mercury-based halides. (August 2022) - Sahoo, Sushree Sarita; Sharma, Vineet Kumar; Gupta, Mayanak K.; Mittal, Ranjan; Kanchana, V.
Abstract: This work presents a theoretical investigation of mercury-based halides in both bulk and monolayer form. These compounds are direct bandgap semiconductors in bulk and monolayer form as it is evident from the analysis of structural and electronic properties. Birefringence values have been used to ascribe anisotropic optical properties, which may host future opto-electronic device applications. The values of mobilities for both the carriers in HgI 2 are consistent with the experimental values. The low value of lattice thermal conductivity and favorable carrier mobilities provide a better scope for thermoelectric properties. The least bandgap of HgI 2 further enables thermoelectric applications, and the thermopower is found to be high with a value of 580 μ V/K for holes and nearly 320 μ V/K for electrons. The thermoelectric efficiency for holes is quite appreciable with a figure of merit zT around 0.5 at 300 K for a carrier concentration of 10 19 cm −3 . In case of monolayers, the thermopower of HgI 2 monolayer is found to be higher than its bulk counterpart. Our findings show that these compounds have robust transport and optical properties, which await future experimental verifications. Highlights: Electronic structure properties of mercury-based halides are calculated which reveal them to be direct bandgap semiconductors. The anisotropic optical properties are ascribed through birefringence values (0.27 for both HgCl 2 and HgBr 2 ), implying future optoelectronic applications evident from these compounds. Our calculated values of carrier mobility are consistent with the experimental values for both electrons and holes in HgI 2 . The low lattice thermal conductivity value is predicted through Slack model and the calculated figure of merit of HgI 2 is found to be around 0.5 for holes at 300K. The monolayers are also direct bandgap semiconductors and could be a better choice for future thermoelectric devices as the thermopower of monolayer HgI 2 is higher than that of bulk for holes at 300K.